An efficient phenylaminecarbazole-based three-dimensional hole-transporting materials for high-stability perovskite solar cells. (November 2020) - Wu, Yuling; Zhang, Weixuan; Qian, Fang; Zhao, Haocheng; Guo, Kunpeng; Wang, Mixue; Li, Xuefeng; Liu, Zhike; Wang, Hua; Xu, Bingshe
Abstract: Hole-transport materials (HTMs) are the key material for preparing high-performing perovskite solar cells (PSCs). Herein, we present a novel and efficient hole-transporting material, 9, 9-dioctyl fluorenyl phenylamine carbazole linked methoxy triphenylamines (CzPAF-OMeTAD), which was synthesized via Buchwald–Hartwig amination reactions from very cheap raw materials such as phenylcarbazole with 9, 9-dioctyl fluorene bridge and arylamine terminals. It is demonstrated the synthesized CzPAF-OMeTAD with 9, 9-dioctyl fluorene as bridge shows a higher hydrophobic and further induce a higher water contact angle of 91° relative to that (79°) for commonly Spiro-OMeTAD with spirofluorene linked methoxy triphenylamines. Further, CzPAF-OMeTAD also exhibits a deeper highest occupied molecular orbital (HOMO) energy level of −5.30 eV and a higher hole mobility of 3.83 × 10 −5 cm 2 V -1 S −1, indicating a potential hole-transport material for high-performance perovskite solar cells. Thus, PSCs were fabricated by using the CzPAF-OMeTAD as HTMs, and the resulting cell demonstrates a high power conversion efficiency (PCE) of 15.35% and very high stability. For example, after 20 days of aging with relative humidity of 60%, the PCE still exhibit retention more than 87% of their initial values for corresponding cell. These are ascribed to the improved film-forming ability by sufficient amount of alkyl chains in CzPAF-OMeTAD and a higher hole-mobility for CzPAF-OMeTAD. These results implied our current research provides huge potential direction in the development of highly efficient and stable PSCs with further optimizing HTMs in the future. Graphical abstract: The CzPAF-OMeTAD-based HTMs exhibit low-costs, homogeneous film-formation abilities, high-hydrophobicity, suitable energy levels, good conductivity, high hole-extraction/transport ability and excellent device stability with PCE still reaching 87% of their initial values after 20 days of aging with relative humidity of 60%. Image 1 Highlights: CzPAF-OMeTAD with 9, 9-dioctyl fluorene as bridge shows a higher hydrophobic. A higher water contact angle of 91° relative to commonly Spiro-OMeTAD (79°). CzPAF-OMeTAD exhibits a deeper HOMO level and a higher hole mobility. High device stability with PCE reaching 87% after 20 days of aging with relative humidity of 60%.